2018
DOI: 10.1073/pnas.1720950115
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of costimulation by human cytomegalovirus promotes evasion of cellular immune defenses

Abstract: CD58 is an adhesion molecule that is known to play a critical role in costimulation of effector cells and is intrinsic to immune synapse structure. Herein, we describe a virally encoded gene that inhibits CD58 surface expression. Human cytomegalovirus (HCMV) UL148 was necessary and sufficient to promote intracellular retention of CD58 during HCMV infection. Blocking studies with antagonistic anti-CD58 mAb and an HCMV UL148 deletion mutant (HCMV∆UL148) with restored CD58 expression demonstrated that the CD2/CD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 56 publications
0
83
0
Order By: Relevance
“…Indeed, the CD2/CD58 pair spatially segregates from LFA‐1/ICAM‐1 complexes, which are found surrounding areas of TCR/pMHC interactions . Consistent with the role of CD2 in promoting close contact formation and hence TCR/pMHC interactions, it has been shown that HCMV can specifically reduce CD58 expression leading to reduced recognition of infected cells by CD8 + T cells . Additionally, knockout of CD58 in cancer cell lines can impair recognition and cytolysis by CD8 + T cells …”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 66%
“…Indeed, the CD2/CD58 pair spatially segregates from LFA‐1/ICAM‐1 complexes, which are found surrounding areas of TCR/pMHC interactions . Consistent with the role of CD2 in promoting close contact formation and hence TCR/pMHC interactions, it has been shown that HCMV can specifically reduce CD58 expression leading to reduced recognition of infected cells by CD8 + T cells . Additionally, knockout of CD58 in cancer cell lines can impair recognition and cytolysis by CD8 + T cells …”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 66%
“…However, the foldincrease in E max and the fold-decrease in EC 50 were largest for CD2 and not for the more canonical co-stimulation receptor CD28, whereas CD27 exhibited only modest fold-changes. Although CD2 was initially reported to have only subtle role in T cell activation in mice (25,26), it is increasingly clear that it is important for human T cell activation (21,27,28) and may be particularly important for CD8 + T cells that do not express CD28 (29). Although co-stimulation in this reductionist system clearly controlled the antigen threshold for T cell cytokine production, it appeared to do so similarly for different cytokines.…”
Section: Discussionmentioning
confidence: 88%
“…However, it is unclear whether this immunosuppression is universal or restricted to immune responses targeting tumour antigens. Recent data in CMV‐infected human cells showed that UL148‐induced down‐regulation of CD58 (a cell surface molecule important for co‐stimulation of effector T cells) leads to dampening of a productive immune response, which includes loss of cytotoxic activity by cytotoxic lymphocytes and natural killer cells . This may be augmented with down‐regulation of APM‐associated components to subdue the immune response .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 99%
“…Recent data in CMV-infected human cells showed that UL148-induced down-regulation of CD58 (a cell surface molecule important for co-stimulation of effector T cells) leads to dampening of a productive immune response, which includes loss of cytotoxic activity by cytotoxic lymphocytes and natural killer cells. 142 This may be augmented with down-regulation of APM-associated components to subdue the immune response. 143,144 This may represent a general mechanism of immune suppression employed by CMV which may also be relevant to cancer.…”
Section: Other Cancersmentioning
confidence: 99%